Effect of C60 Fullerene Aqueous Colloidal Solution on Epithelium after Skin Cryodestruction - Vlasov, Oleksandr O.; Kovalov, Gennadiy O.; Myroshnychenko, Mykhailo S. (Problems of Cryobiology and Cryomedicine, 2018)
Â  Probl Cryobiol Cryomed 2018; 28(2): 170